KAJIAN KEMATANGAN LAYANAN TEKNOLOGI INFORMASI PADA SMKN 5TANGERANG MENGGUNAKAN FRAMEWORK COBIT 4.0 - Handayani, Rani Irma (LPPM Universitas Nusa Mandiri, 2014)
In education, the advancement of information technology has also contributed significantly. This study aims to provide an assessment of IT governance exists and provide an IT management model proposed for SMKN 5 Tangerang created by the study authors refer to the standard COBIT (Control Objectives for Information and Related Technology) Version 4.0. Methodology The study was conducted through the analysis and identification of the vision, mission and goals of the organization SMKN 5 Tangerang, further identification of the function of the IT asset management awareness in support of the achievement of the vision and mission of the company through a questionnaire. From these data, we can both see the target maturity ( maturity level expected ) corresponding to 5 SMKN Tangerang. This study was followed by assessing the maturity level of current through questionnaires and interviews relating to the management of IT respondents. Expected and current data of each IT process maturity level and then analyzed to see gaps, and further defined the steps that must be done to address this gap .